1978
DOI: 10.1111/j.1365-2842.1978.tb01208.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of the curing cycle on some properties of a polymethylmethacrylate denture base material

Abstract: The properties of a denture base material may be modified by altering both the temperature and the time of heating during the curing cycle. In this study a polymethylmethacrylate denture base containing no crosslinking agent was polymerised using four different curing cycles. The structure of the materials so obtained was investigated by an acid etching technique. The materials were characterized with respect to degree of cure, strength and water sorption. It was concluded that: 1. No correlation was observed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
51
1
9

Year Published

1981
1981
2012
2012

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 77 publications
(65 citation statements)
references
References 5 publications
4
51
1
9
Order By: Relevance
“…However, the possibility of leaching residual monomer increases as the water absorption increases. 26 Nevertheless, this polymeric system is suggested to be used for a temporary use with well documented biologically satisfactory characteristics. 11,27 Interestingly, a significant positive correlation between the water uptake measured in this study and the amount of drug leached reported previously was detected for all drugs.…”
Section: Discussionmentioning
confidence: 99%
“…However, the possibility of leaching residual monomer increases as the water absorption increases. 26 Nevertheless, this polymeric system is suggested to be used for a temporary use with well documented biologically satisfactory characteristics. 11,27 Interestingly, a significant positive correlation between the water uptake measured in this study and the amount of drug leached reported previously was detected for all drugs.…”
Section: Discussionmentioning
confidence: 99%
“…This fact is attributed to differences in the residual monomer levels due to the distinct polymerization cycles, considering that the hardness should establish an inversely proportional relationship with the amount of residual monomer (15).…”
Section: Discussionmentioning
confidence: 99%
“…The nature and duration of the conditions to which the molded acrylic resin subjected is described as the polymerization cycle 14,26 . The conventional method of polymerization cycle is a long, slow-temperature water-bath polymerization where the heat-polymerization of acrylic resin is processed for 9 h at 74ºC 26 .…”
Section: Introductionmentioning
confidence: 99%
“…The conventional method of polymerization cycle is a long, slow-temperature water-bath polymerization where the heat-polymerization of acrylic resin is processed for 9 h at 74ºC 26 . There are also post-polymerization cycles such as terminal boiling at 100ºC for durations of 30 min (short-term) or longer than 1 h (long-term) 10,12,14,32 . Furthermore, it has been reported that total polymerization time shorter than 2 h is widely preferred than the long polymerization cycles 3 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation